Narrating and Navigating Authorities: Evangelical and Mainline Protestant Interpretations of the Bible and Science - Chan, Esther (Journal for the scientific study of religion, 2016)
Research on the way Protestants interpret the Bible in relationship to science has tended to focus on biblical literalists; less research, however, has examined the heterogeneity of how nonliteralists interpret the Bible. Utilizing data from semi-structured interviews with 77 evangelical and mainline Protestants who attend high-SES congregations, we find that members of both groups draw on similar interpretation strategies in discussing the Bible and evolution. Both eschew literal interpretations of the Bible, demarcate boundaries between the Bible and science, and subsume evolution under broader theological beliefs. Mainline Protestants and evangelicals differ in the way they interpret miracles, with mainline Protestants revealing more openness to scientific and social interpretations of the Bible's miracles, while evangelicals emphasize God's authority over nature. Findings show that different strategies are evoked depending on the issue discussed, revealing implications for a deeper understanding of the way different traditions provide resources for interpreting the Bible and its relationship to scientific issues. Finally, findings contribute to a more robust knowledge of boundary work between the Bible and science as institutional and epistemic authorities.